Implementasi Akad Murabahah pada Perbankan Syariah - Zaenafi Ariani; Sulpiati Sulpiati (Journal of Sharia Economy and Islamic Tourism, 2023)
Abstract: The murabahah contract is a sale and purchase agreement in sharia banking which is often used for financing. The basic principle of murabahah is that the seller (bank) informs the buyer (customer) of the cost of goods along with the profits they wish to obtain. This research aims to analyze the implementation of murabahah contracts in sharia banking. The research results show that murabahah contracts are widely applied in various sharia banking products, such as financing for vehicles, property and working capital. The advantage of murabahah is that it provides certainty for customers regarding prices and profits obtained by the bank. However, there are several challenges in its implementation, such as customers' lack of understanding of murabahah contracts and the complexity in determining the cost of goods. This research suggests that there is a need to increase sharia financial literacy for customers, as well as develop a more integrated information system to simplify the process of determining the cost of goods. Thus, murabahah contracts can be a more effective instrument in supporting the growth of sharia banking.Abstrak: Akad murabahah merupakan salah satu akad jual beli dalam perbankan syariah yang sering digunakan untuk pembiayaan. Prinsip dasar murabahah adalah penjual (bank) menginformasikan harga pokok barang kepada pembeli (nasabah) beserta keuntungan yang ingin diperoleh. Penelitian ini bertujuan untuk menganalisis implementasi akad murabahah pada perbankan syariah. Hasil penelitian menunjukkan bahwa akad murabahah banyak diaplikasikan dalam berbagai produk perbankan syariah, seperti pembiayaan kendaraan, properti, dan modal kerja. Keunggulan murabahah adalah memberikan kepastian bagi nasabah terkait harga dan keuntungan yang diperoleh bank. Namun, terdapat beberapa tantangan dalam penerapannya, seperti kurangnya pemahaman nasabah terhadap akad murabahah dan kompleksitas dalam menentukan harga pokok barang. Penelitian ini menyarankan perlu adanya peningkatan literasi keuangan syariah bagi nasabah, serta pengembangan sistem informasi yang lebih terintegrasi untuk mempermudah proses penentuan harga pokok barang. Dengan demikian, akad murabahah dapat menjadi instrumen yang lebih efektif dalam mendukung pertumbuhan perbankan syariah.